2018
DOI: 10.1097/ccm.0000000000003010
|View full text |Cite
|
Sign up to set email alerts
|

Early Electroencephalography Findings in Cardiogenic Shock Patients Treated by Venoarterial Extracorporeal Membrane Oxygenation

Abstract: In patients treated by venoarterial extracorporeal membrane oxygenation, early severe background abnormalities on standard electroencephalography provide important information on neurologic outcome. The lack of sleep transients on continuous electroencephalography reflects the severity of brain dysfunction and might represent an additional prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…In one study, 2 of the 13 adult patients had seizures and required specific antiepileptic medications; all EEGs had a background of predominant theta and delta frequencies and severe encephalopathy (i.e., poor variability and absence of reactivity) was associated with unfavorable neurologic outcome [ 8 ]. In another study including 25 adult patients on V-A ECMO, 95% of patients had a diffuse EEG slowing and 59% had discontinuous or an unreactive background; more severe findings were more frequently observed in patients with poor neurological outcome [ 14 ]. In a larger prospective cohort of V–A ECMO patients, low background frequency and an unreactive EEG were independently associated with poor outcome at 28 days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, 2 of the 13 adult patients had seizures and required specific antiepileptic medications; all EEGs had a background of predominant theta and delta frequencies and severe encephalopathy (i.e., poor variability and absence of reactivity) was associated with unfavorable neurologic outcome [ 8 ]. In another study including 25 adult patients on V-A ECMO, 95% of patients had a diffuse EEG slowing and 59% had discontinuous or an unreactive background; more severe findings were more frequently observed in patients with poor neurological outcome [ 14 ]. In a larger prospective cohort of V–A ECMO patients, low background frequency and an unreactive EEG were independently associated with poor outcome at 28 days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill patients, EEG is widely used to recognize or assess different neurological complications, such as seizure and encephalopathy [ 10 , 11 ], or to prognosticate neurological outcome after an acute brain injury [ 12 , 13 ]. Nevertheless, the use of EEG as neuromonitoring tool in adult ECMO patients has also been reported only in small case-series [ 8 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial bleeding but not ischemic strokes were associated with higher mortality (39). Early severe background abnormalities and the lack of sleep transients on standard and continuous electroencephalography were associated with poor neurological outcome of VA-ECMO patients, suggesting the value of electroencephalography in predicting the neurological outcome in such patients (40). Cerebral near-infrared spectroscopy (NIRS) is a noninvasive monitoring technique that can provide continuous value of forehead regional oxygen tissue saturation, which represents the balance between cerebral oxygen delivery and cerebral oxygen consumption.…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…However, the study did not standardize the timing for initiating EEG monitoring in all their patients. Two studies confirmed that background abnormalities on standard EEG at the early phase (1–3 d) were highly predictive of brain injury and poor outcome in patients on VA ECMO ( 54 , 55 ). Furthermore, the authors also found that a lack of sleep transients on continuous EEG reflects the severity of brain dysfunction and might serve as an additional prognostic marker.…”
Section: Clinical Strategiesmentioning
confidence: 84%